Intracranial solitary plasmacytoma: an unusual presentation - BazÃ¡n Ruiz, Susy; Somocurcio Peralta, JosÃ©; Del Carpio Jayo, Daniel (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2019)
Background. Intracranial solitary plasmacytoma is extremely rare and its location in the clivus is unusual; its clinical presentation is very varied and the diagnostic images are similar to the other tumors in skull-base. Case presentation. 47-year-old woman with initial diagnosis of pituitary macroadenoma, attended with headache, nausea, vomiting, diplopia in the right eye and paralysis of her abducent nerve. She was reoperated by transsphenoidal endoscopic approach, concluding in solitary clivus plasmacytoma by biopsy and immunohistochemistry. Conclusions. Clivus is an unusual location for intracranial plasmacytoma. Early diagnosis, complete study and careful follow-up are required due to its high progression to multiple myeloma.